Effects of seedling dipping and foliar application of nano dap on growth, yield and economics of fine rice (Bangladesh Journal of Botany, 2023)
A field experiment was conducted to assess the effect of seedling dipping and foliar application of phosphorus on growth, yield and economics of fine rice. The experimental results revealed that 75% recommended nitrogen, phosphorus and 100% recommended potassium + seedling dipping with nano di-ammonium phosphate @ 5 ml/litre + foliar spray with nano di-ammonium phosphate @ 4 ml/litre application recorded significantly higher growth, yield and yield attributes, which was statistically at par with, 50% recommended nitrogen, phosphorus +100% recommended potassium + seedling treatment with nano di-ammonium phosphate @ 5 ml/litre+ 2 foliar spray with nano di-ammonium phosphate each @ 4 ml/litre and @ 2 ml/litre and 100% recommended nitrogen, phosphorus and potassium. However, 50% recommended nitrogen, phosphorus +100% recommended potassium + seedling treatment with nano di-ammonium phosphate @ 5 ml/litre+ 2 foliar spray with nano nano di-ammonium phosphate each @ 4 ml/litre recorded significantly highest agro physiological efficiency. However, in terms of economics 75% recommended nitrogen, phosphorus and 100% recommended potassium + seedling dipping with nano di-ammonium phosphate @ 5 ml/litre + foliar spray with nano nano di-ammonium phosphate @ 4 ml/litre recorded highest net returns and benefit cost ratio.Bangladesh J. Bot. 52(4): 1025-1031, 2023 (December)